Lewis & Clark [videorecording (DVD)] : the journey of the Corps of Discovery - Burns, Ken, 1953-; Holbrook, Hal (PBS Home Video, 2004)
Tells the story of the most important expedition in American history, led by Captains Meriwether Lewis and William Clark. Includes the stories of the young army men, French-Canadian boatmen, Clark's African-American slave, and the Shoshone woman named Sacagawea who went with them.